Substation structure design guide - Kempner, Leon (ASCE manuals and reports on engineering practice, 2008)
Prepared by the Subcommittee on the Design of Substation Structures of the Committee on Electrical Transmission Structures of the Structural Engineering Institute of ASCE. Substation Structure Design Guide provides a comprehensive resource for the structural design of outdoor electrical substation structures. This manual offers the most current guidelines available on analysis methods, structural loads, deflection criteria, member and connection design, structure testing, quality control, quality assurance, connections used in foundations, detailing, fabrication, construction, and maintenance. Utility engineers, structural and electrical engineers, and anyone that works in the field of transmission line substation design will benefit from this manual.